Une recherche responsable L'intégrité scientifique - Alunno-Bruscia, Marianne (éditions Quae, 2023)
Scientific integrity is defined by the French Research Code as "the set of rules and values that must govern research activities in order to guarantee their honest and rigorous nature". It applies to all knowledge production and dissemination practices. It is essential not only to the smooth running of scientific communities, and to the robustness and reliability of the knowledge produced, but also to the sustainability of public confidence in science. In France, as in other countries, an institutional and legal framework for research has gradually been established, encouraging all players in the world of research to rigorously exercise their responsibility for self-regulation. This book recalls the essential principles of scientific integrity and the stakes involved in respecting them, as well as the role that each player in research must play. It also outlines the context in which this notion has been mediatized, and suggests ways of building a favorable ecosystem. This book is aimed at students and all research professionals.